Skillset development mobile application (SkillD) - Teo, Alvin Shao Jie (Nanyang Technological University, 2020)
In a time where lifelong learning through personal progress is necessary, many local universities started focusing their attention on the development of individuals’ skills by making student group workshops more accessible to the undergraduates. But it is a challenge for the students as they are unaware if what they have signed up for is actually beneficial to their future. In this project, the author will explore ways to develop a one stop platform for the students to assist their skill development progress on the campus. To achieve this, a mobile application, SkillD will be developed using technologies comprising React Native, Node.js and MySQL. It is hoped that this simple connection would help them to be more aware of the skillsets they have acquired and would support their career development throughout their undergraduate education.